Characteristics of colored dissolved organic matter (CDOM) in the Western Arctic Ocean: Relationships with microbial activities. (August 2015) - Matsuoka, Atsushi; Ortega-Retuerta, Eva; Bricaud, Annick; Arrigo, Kevin R.; Babin, Marcel
Abstract: Colored dissolved organic matter (CDOM), a significant fraction of dissolved organic carbon (DOC), plays various roles in physical and biogeochemical processes in natural waters. In the Arctic Ocean, CDOM is abundant because of major input by large rivers. To better understand the processes that drive variations in CDOM, light absorption coefficients of CDOM [ a CDOM ( λ ), m −1 ] were extensively documented together with temperature, salinity, chlorophyll a, nitrate concentrations, and bacterial production (BP) and abundance (BA) in the Western Arctic Ocean (WAO) from early to late summer as part of the MALINA and the ICESCAPE expeditions. The data set covered contrasting situations, from bloom to post-bloom conditions and from river-influenced to oceanic water masses. While CDOM photobleaching occurred in the surface layer (<20 m), we observed significantly lower spectral slopes for CDOM absorption spectra ( S CDOM ) in addition to higher a CDOM (440) in the layer below (intermediate layer: 30.7<salinity<33.9). In particular, the low S CDOM values were found in the Chukchi Sea and the western part of the Beaufort Sea, which coincided with high BP and BA values. Considering the high primary production observed in these areas during our cruises (Arrigo et al., 2012. Science. 10.1126/science.1215065), we hypothesize that S CDOM variations reflect the degradation of phytoplankton that is associated with heterotrophic bacterial activity. In our datasets, a simple regression analysis showed that S CDOM was significantly correlated with BP and BA. A principal component analysis further supported this conclusion. From our field observations, it was shown that variations in a CDOM (440) and S CDOM result to a large extent from bacterial activity, at least in the WAO.